Medida da resistência das vias aéreas pela técnica do interruptor em crianças nascidas prematuramente - Salomão, Sandra Cristina (2011)
OBJECTIVE : To evaluate the airway resistance by interrupter technique (Rint) in preschool children born prematurely. STUDY DESIGN : Cross-sectional study of cohort premature infants born between (2004-2005). Data collection was conducted from November 2008 and May 2010. Anthropometric measurements were performed on the test day. The Rint was measured with the device Microrint® using filter. Calibration was performed every 50 trials. Were carried out 10 interruptions to the flow air in the peak expiratory flow sequentially. At the end of the test were stored ten consecutive respiratory cycles and to check the acceptability of the examination format of the curves and the VC for reproducibility £ 20%. We used the median value of Rint. RESULTS : The Rint was measured in 33 (89%) preterm infants and compared with a control group of 32 children. The premature group had higher Rint (0.91 kPa/L/s) versus the control group (0.80 kPa/L/s) but not statistically significant (p= 0,832). CONCLUSION : The Rint is easily reproducible in preschool children, but a tool is not sensitive enough to identify obstruction in patients with a history of prematurity in relation to the group of healthy children.